2022
DOI: 10.1001/jamapsychiatry.2022.1640
|View full text |Cite
|
Sign up to set email alerts
|

An Intersectional Approach to Ethnoracial Disparities in Pathways to Care Among Individuals With Psychosis in Coordinated Specialty Care

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…We found that patients who identified as Black or other racial and ethnic groups were more likely to be referred from the ED or bridging clinic and inpatient units compared with White patients. Our findings add to the EPI evidence highlighting racial disparities in service access and use, with numerous studies documenting that Black patients are at higher risk of coercive referral and intervention, involuntary admissions, and emergency service use, relative to other racial and ethnic groups . In past research, these disparities have been explained by delays in help-seeking due to stigma or cultural and/or religious beliefs, mistrust in the medical system because of past negative experiences, racial bias leading to police involvement and coercive intervention, and other structural barriers including poverty and residential instability .…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…We found that patients who identified as Black or other racial and ethnic groups were more likely to be referred from the ED or bridging clinic and inpatient units compared with White patients. Our findings add to the EPI evidence highlighting racial disparities in service access and use, with numerous studies documenting that Black patients are at higher risk of coercive referral and intervention, involuntary admissions, and emergency service use, relative to other racial and ethnic groups . In past research, these disparities have been explained by delays in help-seeking due to stigma or cultural and/or religious beliefs, mistrust in the medical system because of past negative experiences, racial bias leading to police involvement and coercive intervention, and other structural barriers including poverty and residential instability .…”
Section: Discussionsupporting
confidence: 52%
“…Our findings add to the EPI evidence highlighting racial disparities in service access and use, with numerous studies documenting that Black patients are at higher risk of coercive referral and intervention, involuntary admissions, and emergency service use, relative to other racial and ethnic groups. 27 In past research, these disparities have been explained by delays in help-seeking due to stigma or cultural and/or religious beliefs, mistrust in the medical system because of past negative experiences, racial bias leading to police involvement and coercive intervention, and other structural barriers including poverty and residential instability. 5 , 12 , 14 , 28 , 29 These factors may also pose barriers to accessing care for other patients with minoritized race and ethnicity as they were also more likely to be referred from the ED or bridging clinic compared with White patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, examining related concepts, such as an individual’s ethnoracial identity, may improve our understanding of underlying mediating mechanisms. A promising avenue for further inquiry also includes the role of various intersecting characteristics that defines a person’s social position, thereby impacting psychosis liability.…”
Section: Discussionmentioning
confidence: 99%
“…Even though disadvantaged groups, especially Black communities, were more likely to present with psychosis, research shows they are less likely to reach high-quality mental health services, such as coordinated specialty care. 83 Future studies should improve the measurement of race and ethnicity by using more fine-grained measures, especially for the group labeled as other. Furthermore, examining related concepts, such as an individual's ethnoracial identity, may improve our understanding of underlying mediating mechanisms.…”
Section: Discussionmentioning
confidence: 99%